Strategi Kepemimpinan Keterampilan Komunikasi Kepala Kelompok Bermain dalam Masa Studi : Studi Kasus Di KB Aisyiyah 13 Jepara: Strategi Kepemimpinan Keterampilan Komunikasi Kepala Kelompok Bermain dalam Masa Studi : Studi Kasus Di KB Aisyiyah 13 Jepara - Ainur Rosyidah Kusuma; Rizka Suprihatiningsih; Lita Latiana; Ali Formen (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2022)
Everyone has needs, both for themselves and for the fulfillment of the needs of others. This also applies to school principals, especially the head of the Playgroup. So the need for leadership strategies and good communication skills so that the fulfillment of one's own needs does not interfere with the fulfillment of the needs of others. This study aims to determine the leadership strategies and communication skills of the head of the Aisyiyah 13 Jepara Playgroup during the fulfillment of one's own needs during the postgraduate education level. The method used in this research is a qualitative case study to describe communication skills. Based on the results of the research conducted, it was found that there were various kinds of leadership strategies and communication skills of the playgroup heads during the educational study period. However, due to the limited time the head of the playing group had, the supervisory function did not work properly.